Identifying the feasibility of establishing a passive house school in central Europe: An energy performance and carbon emissions monitoring study in Germany. (October 2019) - Wang, Yang; Du, Jiangtao; Kuckelkorn, Jens M.; Kirschbaum, Alexander; Gu, Xin; Li, Daoliang
Abstract: The development of the Passive House (PH) Standard has provided an important opportunity to minimize the energy consumption of buildings in accordance with global targets for climate change and energy savings. This article presents a 3-year monitoring study (operation and optimization) of energy performance and CO2 emissions in a newly built Passive House school building in southern Germany. Monthly, annual and specific energy demands (including heating, cooling and electricity) were analyzed and evaluated using three energy-benchmarking systems: EnEV, LEE and PHPP. Sorted load duration profiles for heating and electricity from 2012 to 2014 have also been presented and assessed. In addition, the CO2 equivalent emission resulting from the total energy consumption of the building was calculated. The results illustrate that the newly built Passive House school building could meet the requirements of the three energy-benchmarking systems and would reduce the total annual CO2 emissions of a standard school building in Germany by up to two-thirds. Highlights: Evaluation on thermal and electric energy performance for a new PH via optimization. Low-energy school building energy performance jointly solved by measurements. More than 3-year measurement results from monitoring system with sensor/meter network. 3 different energy balance methods used for the energy consumption calculation. Climate-adjusted energy requirements for a reference year investigated and compared.